Tocka Apparel / Amirul Faeez Yusri - Yusri, Amirul Faeez (2021)
Tocka Apparel is a new retail venture that will provide one-of-a-kind apparel to members of the millennial age. The founders, Amirul Faeez Bin Yusri, will manage this business, which will be a casual urban wear apparel store. It's a brand-new clothing store that caters to everyone, particularly students. It will be held in the PKNS Kompleks Shah Alam in Selangor. Tocka Apparel has positioned itself precisely in proximity to our target market's home location and social activities. This, we feel, is vital to our long-term success and growth. While our initial objective is to establish one boutique, we hope to expand by franchising our retail location or creating a well-known brand name. As a result, we expect to capture a significant share of the internet retail industry. We plan to give the teens unique clothes that they would not be able to get elsewhere in the state.